The Role of Strategic Alignment in Tourism Package: Questionnaire study of the Views of managers in excellent class hotels in Erbil City - Rana Nissan Yousif; Kosret Muhemed Ebabekir; Mahabat Noori Abdullah (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The current research seeks to know the role of strategic alignment (communication, infrastructure and skills) in Tourism Package. The problem of the research was identified by asking questions about the nature of the relationship and the impact of the variables. A hypothetical scheme was designed to reflect the main hypotheses, and the questionnaire was used as a means of obtaining data, distributed to all persons with the director's job title, and numbered 54 individuals in 9 excellent class hotels in Erbil City. In order to find out the validity of the hypotheses, multiple tests were carried out through using the (SPSS) program. The research followed the descriptive analytical approach in order to reach the goals and to find the relationship between the variables. The research concluded that there was a positive relationship and moral influence between the strategic alignment and the tourism package. Suggested that the strategic alignment components should maintained and used in delivering the package for tourism services through the workshops that supporting the exchange of ideas between Hotel staff